CONNOTATIVE MEANING OF VERBAL AND VISUAL SIGNS IN WHAT CAN’T MILK DO? ADVERTISEMENT - Ayu Meriandari, Ni Rai; Dian Puspita Candra, Komang; Andri Permana, I Putu (TANDA, 2022)
This research is entitled Connotative meaning of verbal and visual sign in “What Can’t Milk Do?” Advertisement. This study is conducted with the aims to analysed the connotative meaning of verbal and visual signs contain in “What Can’t Milk Do?” advertisement. Verbal and visual communication tools that are used by human to interact, whether through messages, sounds, pictures, and gestures. The data were taken from the YouTube platform. The data were collected by observation method. The analysis was done by the descriptive qualitative method. The study started by analysing verbal and visual signs which is based on the theory of semiotic by Saussure (1893). Then, the analysis of the connotative meaning of the verbal and visual signs was done by using the theory of meaning proposed by Barthes (1977). In addition, the study of colors was done using the approach of color term submitted by Wierzbicka (1996). The connotative meaning from this advertisement want to remind the viewers that milk is not only just an ordinary beverage but it can turn you into a morning person and get you through tough tasks, while also forming the basis for everything from health-conscious food or to decadent desserts and from the advertisement we can found verbal and non-verbal sign and the meaning of an advertisement.